Ediacaran emerald mineralization in Northeastern Brazil : the case of the Fazenda Bonfim deposit - Santiago, Judiron Santos (2019)
The Fazenda Bonfim emerald deposit lies within the Seridó Belt. It is a classic example of deposit formed through metasomatic interactions between Be-rich granite intrusions and Cr(± V)-rich mafic-ultramafic rocks. The setting of the emerald mineralization was built under strong strike-slip dynamics, which produced serpentinization and talcification of mafic-ultramafic host-rocks, and was followed by syn-kinematic emplacement of Be-rich albite granite, favoring hydrothermal/metasomatic processes. The structural control and lithological-contrast were fundamental to the fluid flow and the best ore-shoot geometry, developed in the S-foliation intra-plane at the contact zone (phlogopite hornfels) between mafic-ultramafic rocks and the albite granite. Subsequently, an albitization process, linked to the final-stage of magmatic crystallization, led to an overall mineralogical and chemical change of the albite granite. 207U-235Pb data revealed inheritance ages from Archean to Neoproterozoic and a crystallization age of 561 ± 4 Ma for albite granite. However, 40Ar/39Ar data revealed plateau age of 553 ± 4 Ma for phlogopite hornfels, interpreted as the closure time for the metasomatic event responsible for the nucleation and growth of emerald crystals. The short interval of time between U-Pb and Ar-Ar data indicates an intense, but not protracted, metasomatic history, probably due to low volume of intrusive magma.